PENGARUH JUMLAH DESA YANG MEMILIKI FASILITAS SEKOLAH TERHADAP PENDUDUK BUTA HURUF DI PROVINSI KEPULAUAN BANGKA BELITUNG - Elly Okta Lina (STAI Hubbulwathan Duri, 2019)
This study aims to find out how the development of the number of villages that have school facilities in the Province of Bangka Belitung Islands, and analyze the development of the percentage of illiterate population in the Bangka Belitung Islands Province, compare it with the percentage of national illiterate population and analyze the influence of the number of villages that have school facilities on blind residents letters in the Province of Bangka Belitung Islands. This research is a quantitative study, using statistical analysis with linear regression data analysis techniques and validation tests of ANOVA analysis. This research uses data from the pages of the Bangka Belitung Islands Provincial Statistics Agency from 2011 to 2018. Based on the research that has been done, it can be concluded that there has been an increase in the number of villages that have school facilities in the Bangka Belitung Islands Province of 32% to 36% in contrast The percentage of illiterate people in the Bangka Belitung Islands Province has decreased from 17.41% to 2.91%. This 2.91% figure is lower than the national percentage of 4.88%. Based on regression analysis with a regression coefficient of 0.940 and the regression equation Y = -0.860X + 128.2 and ANOVA analysis with a p-value of 0.0038 and significance 0.0049 can be concluded a variable increase in the number of villages that have school facilities resulting in a decrease variable percentage of illiterate population in Bangka Belitung island province.